Analysis of role performance of women in farm activities under KVK Mokokchung, Nagaland - Pijush Kanti Biswas; Bendangjungla.I; Ruyosu Nakro, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The study was undertaken in Mokokchung district of Nagaland. A total of 50 farm women selected as respondents through proportionate random sampling.The selected respondents were interviewed personally using pre-tested well structured interview schedule. The data were analysed using appropriate statistical tool.The findings showed that farm women’s participation was maximum in weeding, picking, drying of grains, cleaning of grains and processing and major part of cleaning of field, thinning, shifting production of threshing floor, marketing, grading and gap filling.